2018
DOI: 10.3390/ph11020044
|View full text |Cite
|
Sign up to set email alerts
|

Old Drugs as New Treatments for Neurodegenerative Diseases

Abstract: Neurodegenerative diseases are increasing in number, given that the general global population is becoming older. They manifest themselves through mechanisms that are not fully understood, in many cases, and impair memory, cognition and movement. Currently, no neurodegenerative disease is curable, and the treatments available only manage the symptoms or halt the progression of the disease. Therefore, there is an urgent need for new treatments for this kind of disease, since the World Health Organization has pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
167
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(170 citation statements)
references
References 121 publications
0
167
0
3
Order By: Relevance
“…Galantamine, an alkaloid extracted from Galanthus species, is a currently prescribed AChE inhibitor drug for AD and dementia [94,97]. Other promising secondary metabolites of note with AChE inhibitory activity are crocin, EGCG and naringin.…”
Section: Acetylcholinesterase Inhibition Activitymentioning
confidence: 99%
“…Galantamine, an alkaloid extracted from Galanthus species, is a currently prescribed AChE inhibitor drug for AD and dementia [94,97]. Other promising secondary metabolites of note with AChE inhibitory activity are crocin, EGCG and naringin.…”
Section: Acetylcholinesterase Inhibition Activitymentioning
confidence: 99%
“…To date, there is no cure for neurodegenerative diseases, and all available treatments only manage symptoms or halt disease progression. Drug repurposing, which is the evaluation of existing drugs normally used to treat other diseases such as cancer, asthma, infections and others for their therapeutic potential in treating neurodegenerative diseases, is an active area of research with the advantage of already pre-existing knowledge about the pharmacokinetic and pharmacodynamic profiles of drugs [142]. Beyond repurposing existing drugs, further research on molecular mechanisms and potential new therapies for neurodegenerative diseases is desirable.…”
Section: Targeted Proteolysis Via Lysosomes or The Ermentioning
confidence: 99%
“…Besides, they showed that Crocin treatment significantly reduced plasma amounts of IL‐1β, IL‐6, and TNF‐α in CIA mice. Therefore, their study proved that Crocin can inhibit the production of IL‐1β, IL‐6, and TNF‐α by inhibiting the nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) activation via its interaction with inhibitor of nuclear factor kappa kinase (IKK) …”
Section: Ramentioning
confidence: 99%
“…Therefore, their study proved that Crocin can inhibit the production of IL-1β, IL-6, and TNF-α by inhibiting the nuclear factor kappa-light-chainenhancer of activated B cells (NF-κB) activation via its interaction with inhibitor of nuclear factor kappa kinase (IKK). 51 Hemshekhar et al studied the antiarthritic effects of Crocin. They found that Crocin efficiently neutralized the increased serum amounts of enzymatic (MMP-3, MMP-9, MMP-13 and hyaluronidases) and non-enzymatic (IL-1b, Cyclooxygenase-2:COX-2, Prostaglandin E2:PGE2, NF-kB, IL-6, TNF-a, and ROS) inflammatory mediators.…”
Section: Ramentioning
confidence: 99%